PENGARUH TINGKAT PENDIDIKAN, PENGALAMAN KERJA DAN INSENTIF TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PADA CV. KARYA MINA PUTRA DIVISI IKAN KERING REMBANG - Liasiska, Irma; Nurhidayati, Anik (JAB (Jurnal Akuntansi & Bisnis), 2018)
The development of the business world in Indonesia is currently experiencing a fairly tight competition. And this is a big challenge in the current era of global trade. Businesses that can survive are only those who are responsive in improving quality, efficient and able to anticipate market wants and needs. Therefore it is necessary for employees who have a high level of work productivity so that production can be achieved in accordance with the target. Employees are assets that play an important role in the company, so it is necessary to note the level of education, work experience and incentives that will be given to them. These three things will influence the mindset, attitude and behavior and are believed to influence their productivityThe purpose of this study was to determine the effect of the level of education, work experience and incentives on the work productivity of the production employees of CV. Karya Mina Putra Rembang dried fish division. For the sample of this study were 30 people who became respondents. The data collection technique in this study was through a questionnaire. While the sampling technique uses cluster sampling and convenience sampling techniques.The variable level of education tcount is smaller than t table (0.813> 1.665) which means the level of education has no significant positive effect on work productivity, work experience of tcount is greater than ttable (3.629> 1.665) which means work experience has a positive and significant effect on work productivity, incentives tcount is greater than t table (2,535> 1,665) which means that incentives have a positive and significant effect on work productivity.Keywords: level of education, work experience, incentives, work productivity.